Clinical Relevance of NGAL/MMP-9 Pathway in Patients with Endometrial Cancer - Aneta Cymbaluk-Płoska (Disease Markers, 2017)
The objectives of the study were to assess the relationship between the serum levels of MMP-9 and NGAL and the clinical staging and histopathological grade of the tumor. Lipocalin-2/NGAL and MMP-9 concentrations were quantified in serum by multiplex fluorescent bead-based immunoassays (Luminex Corporation, Austin, TX, USA). The AUC values for NGAL and MMP-9 were 0.9 and 0.78, respectively. The diagnostic potential of NGAL and MMP-9 in differentiating high-stage (FIGO III and IV) and low-stage (FIGO I and II) cancer and predicting the cell differentiation grade (G1 versus G3) on the basis of the analyses of AUC values was determined to be 0.91 and 0.79 for NGAL and 0.82 and 0.84 for MMP-9, respectively. Multifactorial logistic regression analysis in the final method revealed that NGAL and MMP-9 variables were independent of the endometrial cancer risk. OR values for NGAL and MMP-9 were 1.23 (95% CI 1.421–3.27; p=0.034) and 1.09 (95% CI: 1.38–4.12; p=0.026), respectively. The NGAL/MMP-9 complex may be useful in the assessment of tumor stage before surgical treatment.